Historic breakthrough for social and solidarity economy at the International Labour Organization - Hamish Jenkins (United Nations Research Institute for Social Development (UNRISD), 2023)
For more than two decades, a growing global movement has been promoting the social and solidarity economy (SSE) as a viable alternative socioeconomic approach to the manyfold challenges of sustainable development. This growing movement has been advocating for the UN system and its member states to adopt SSE in their development policy strategies. In a historic breakthrough, the International Labour Conference of the International Labour Organization (ILO) at its 110th session in June 2022 held, for the first time, a general discussion on decent work and the social and solidarity economy. This landmark event was also the first high-level debate in the UN system on the subject. This working paper provides an analytic overview of some of the major political and substantive achievements of the ILO resolution, as well as some of its limitations and elements that were not (or not sufficiently) addressed in this first global policy document on SSE. The paper benefitted from the insights and contributions of SSE organizations and experts that followed closely the negotiations.
Keywords: 330; Sozialwirtschaft; Arbeitsrecht; Welt